KORELASI PETUAH BUGIS PAPPASENG DENGAN HADIS-HADIS TARBAWI (TELAAH CATATAN MAPPIASSE GULE DALAM 100 ADA-ADA PAPPASENG TORIYOLO) - Agustang K (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2018)
“Pappaseng” is an oral literature spoken by “to riyolo na Ugi'e” (ancestor of the Bugis tribe) to give a message to “ana 'monri'e” (young generation) so as not to fall into the things that are not desirable. While the Quran and the hadth is a way of life for Muslims that contains values from all aspects of human life, including the one is about moral messages, ethics and rule of interaction. Both become the basis of life of Bugis tribe people in living their lives and interact with each other. This research is a qualitative research with a cultural approach to search for the educational hadith relationship with the advice “Bugis pappaseng” form as a repertoire of science in the Bugis society. And obtained the result that the value contained in “pappaseng” always connected directly with the content of the educational hadith, such as courage, honesty, work ethic of faith and so forth.